Theory and Practice in Socialist Economics - Lerner, A. P. (Review of Economic Studies, 1938)
Journal Article Theory and Practice in Socialist Economics Get access A. P. Lerner A. P. Lerner London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 1, October 1938, Pages 71–75, https://doi.org/10.2307/2967541 Published: 01 October 1938